Pengaruh model pembelajaran Li-Pro-GP terhadap kesadaran metakogitif dan kemampuan pemecahan masalah IPA biologi SMP - Zaskia, Alia; Pantiwati, Yuni; Fauzi, Ahmad; Wahyuni, Sri; Permana, Tutut Indria (Biosfer: Jurnal Pendidikan Biologi, 2025)
21st century learning demands the development of metacognitive awareness and problem-solving skills, but science learning in schools is still predominantly teacher-centered. This study aims to determine the effect of the Li-Pro-GP learning model (project-based literacy integrated with school literacy movement and character education) on metacognitive awareness and problem solving skills in Biology science learning. The research used a quantitative approach with a non-equivalent control group quasi-experimental design. The sample consisted of VIII grade students in one of the private junior high schools in East Java, with VIII A as the control and VIII B as the experiment. The research instruments used included questionnaires to measure metacognitive awareness, essay questions to assess problem solving skills, and observation sheets to assess learning implementation. Data analysis was conducted using ANCOVA with the help of SPSS 26. The post-test results showed higher scores in the experimental class than the control for both variables. ANCOVA test showed a significant effect of Li-Pro-GP model on metacognitive awareness [F(1,57) = 129.926, p = 0.000, ηp² = 0.695] and problem solving skills [F(1,57) = 81.481, p = 0.000, ηp² = 0.588]. The results of the analysis showed a significant difference and a large effect size, so it can be concluded that the Li-Pro-GP model can improve students' metacognitive awareness and problem solving skills in learning Biological Science.